PENGARUH STRUKTUR ORGANISASI TERHADAP KUALITAS PELAYANAN PUBLIK (Suatu Studi Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Halmahera Utara) - PALIEMA, DESTRINA; Mandey, Jantje; Ogotan, Martha (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: This study aimed (1) to describe the condition of the organizational structure and quality of publicservices in the Department of Population and Civil Registration Regency of North Halmahera. (2) to analyze theeffect of organizational structure on the quality of public services in the Department of Population and CivilRegistration North Halmahera Regency.This research uses descriptive method with quantitative approach. Samples were drawn by purposive sampling ofrespondents as many as 33 employees / personnel services, and 33 other respondents are elements of servicerecipients, then spread Questionnaire (questionnaire) and the results are analyzed by applying descriptivestatistical analysis techniques and simple regression analysis and correlation of product moment.Results of the study were presented as follows: (1) Organizational Structure Office of Population and Civil NorthHalmahera Regency is in the category "medium" or reasonably support the achievement of the quality of publicservices, while the quality of public services, according to respondents element employees perceive higher thanrespondents element of the user community services which can only perceive the "moderate" or medium. (2) Theorganizational structure has positive influence on the quality of public services. That means that if theorganizational structure optimally managed, it will boost the quality of public services, particularly in theDepartment of Population and Civil North Halmahera.Thus, it can be concluded that the hypothesis which states "The organizational structure of positive andsignificant impact on the quality of public services at the Department of Population and Civil North Halmaheravalidity can be tested empirically, as well as justify terori-the underlying theory.Keywords: organizational structure, quality of public service